Development of the SAPA JADI Sexual Education Media as a Big Board Game to Improve Knowledge on Sexual Harassment - Nurhaliza, Sheila; Tasu'ah, Neneng (BELIA Early Childhood Education Papers, 2025)
In cases of sexual harassment that have occurred, both victims and perpetrators are not limited to adults but also include children. The existence of such acts of sexual harassment highlights the urgency of implementing child protection efforts. One preventive measure to reduce cases of sexual harassment is by increasing children's knowledge of sexual harassment from an early age. Therefore, this study aims to develop a sex education medium in the form of a board game to improve young children's understanding of sexual harassment. This medium is designed to help learners and educators comprehend three essential aspects of sex education: recognition of body parts, identification of body parts that may and may not be touched, and appropriate ways to act, react, and speak in situations with tendencies of sexual exploitation. The development method used is Research and Development (R&D), which includes the stages of identifying potential and problems, data collection, product design, design validation, design revision, limited product trials, product revision, and large-scale product testing conducted with 30 kindergarten B students at TK Al-Hikmah Krasak. The trial results show that the SAPA JADI sex education big board game has a significant impact on increasing students' knowledge regarding sexual abuse prevention